1991
DOI: 10.1085/jgp.97.5.913
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between Q gamma and Ca release from the sarcoplasmic reticulum in skeletal muscle.

Abstract: Asymmetric membrane currents and fluxes of Ca 2+ release were determined in skeletal muscle fibers voltage clamped in a Vaseline-gap chamber. The conditioning pulse protocol 1 for suppressing Ca z+ release and the "hump" component of charge movement current (I~), described in the first paper of this series, was applied at different test pulse voltages. The amplitude of the current suppressed during the ON transient reached a maximum at slightly suprathreshold test voltages (-50 to -40 mV) and decayed at higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
99
4

Year Published

1992
1992
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(116 citation statements)
references
References 41 publications
13
99
4
Order By: Relevance
“…The latter observations reinforced a scheme that required only a single (qt) intramembrane charge species that had a relatively shallow voltage dependence (k ~ 11-15 mV; Pizarro et al, 1991). This could trigger an initial release of intracellularly stored Ca z+ into the space between transverse tubules and sarcoplasmic membrane.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…The latter observations reinforced a scheme that required only a single (qt) intramembrane charge species that had a relatively shallow voltage dependence (k ~ 11-15 mV; Pizarro et al, 1991). This could trigger an initial release of intracellularly stored Ca z+ into the space between transverse tubules and sarcoplasmic membrane.…”
Section: Discussionsupporting
confidence: 56%
“…Such schemes were prompted by the observations of late inward-going phases that followed "humps" isolated from ON charge movement waveforms, as these could reflect the subsequent diffusion of Ca 2+ away from that space. There were also the complexities observed in the biphasic OFF charge movements and their smaller integrals compared with the ON transients Pizarro et al, 1991;Szucs et al, 1991;see also Hui, 1994). However, the experimental conditions adopted here resulted in complete decays to steady DC levels without intervening inward-going phases or other time-dependent currents.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…During the past 30 years, many properties of SR Ca release have been elucidated from studies on intact, cut, and skinned fibers, on iso-lated triads and SR vesicles, and on single SR Ca channels incorporated into lipid bilayers, as reviewed by Rios and Pizarro (1991), Schneider (1994), Meissner (1994), and Franzini-Armstrong andJorgensen (1994). The studies in intact and cut fibers have shown that the rate of Ca release from the SR into the myoplasm is under the control of the voltage across the membranes of the transverse tubular system.…”
Section: Introductionmentioning
confidence: 99%